Focus on IFPRI ... International Food Policy Research Institute - International Food Policy Research Institute (2000)
This article provides a general overview of the mission of IFPRI and highlight steps that are essential to close the gap between food production and food demand in the 20th century. It includes reviews of two 1999 IFPRI publications, World Food Prospects and Livestock to 2020. The World Food Prospects is also featured as a recent publication elsewhere in the newsletter.